Optimization of Transaction Processing System (TPS) Using RAD With FAST Method - Sofyan, Yusuf; Fitriani, Wirda; Kurniawan, Heri (International Journal of Science, Technology & Management, 2022)
The use of computer-based information systems today has been understood by most companies in order to survive and succeed well. The transaction processing system (TPS) is a computerized system that runs and records daily routine business transactions that serve the operational level in the company. Information systems of purchase, inventory, sales are part of the TPS widely used by companies. The problem here is how to ensure that the system is connected to the organization's business plan and information requirements, where often a system that is built is not in accordance with the wishes of the user. Meanwhile, manual information systems can cause problems such as data redundancy, inconsistent data, irregular recording, miscalculations, difficulty in finding data and delays in presenting reports. To build the information system, the Framework for the Application of System Thinking (FAST) method will be used with a Rapid Application Development (RAD) approach that uses selected prototype features. The solution is expected to build an information system that can bring together user requirements and help companies process purchase, inventory and sales data in an integrated manner, so as to increase the efficiency and effectiveness of retail data processing.